Structure Design and Simulation Analysis of the Lower Limb Wearable Walking Aid - Wang Xin; Yan Peifeng (Jixie chuandong, 2024)
A wearable walking aid for lower limbs is designed, which is mainly used to assist patients with lower limb movement disorders such as stroke hemiplegia to carry out daily walking activities. First of all, based on the analysis of the lower limb motion mechanism, joint structure and the composition of degrees of freedom, the three-dimensional structure model of the lower limb wearable walker is established. The 3D infrared motion capture system is used to collect the gait data of normal people and fit the corresponding joint angle curve. The simplified D-H model of the walker is established, and the kinematics modeling analysis of the walker is carried out. Taking the gait data collected from the motion capture experiment as the simulation driving force, the kinematics simulation verification of the walker is carried out. The results show that the joint angle change curve is basically consistent with the angle curve collected from the experiment, and the angular velocity change curve and the ankle joint centroid position change curve are consistent with the normal human walking law, which verify the rationality of the structure design of the lower limb wearable walker.